ANALISIS PERBEDAAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SAHAM SEBELUM DAN SESUDAH PERISTIWA GEMPA DI YOGYAKARTA TANGGAL 27 MEI 2006 (Sudi Kasus pada Perusahaan Asuransi Terdaftar di Bursa Efek Jakarta) - Istanti, SE., MM.,, Lulu Nurul (IQTISHODUNA, 2007)
This research presents an empirical analysis of difference between abnormal return and trading volume activity before and after earths-quake, in Yogyakarta at May 27, 2006. And examine its statistical properties. This research argues that there was difference between abnormal return and trading volume activity before and after quake. For this purpose, the mean difference test, using t-test, was applied to compare the mean value of abnormal return and trading volume activity before and after quake. The sample of this research consists of the insurance firms listed at the Jakarta Stock Exchange. Investigation on the sample firms involved periods of ten days before quake and ten days after quake. The results of this research indicate that there was no significant difference between the abnormal return and trading volume activity before and after quake. This evidence confirms that even did not positively influence abnormal return and trading volume activity as suggested theoretically. Â